Distribution of Ammannia auriculata (Lythraceae) in Kanto District according to herbarium specimens - Hayakawa, Hiroshi (Journal of Weed Science and Technology, 2024)
Ammannia auriculata Willd. is an annual naturalized weed native to North America. Since around 2000, the distribution of this species has expanded from western Japan to the Kanto District. Specimens were surveyed to examine the naturalization status of this species in the Kanto District, which is the current eastern limit of the distribution of A. auriculata in Japan. Only one specimen of A. auriculata collected from Kanto District was found among 19 herbaria. Specimens in at least one prefecture were erroneously identified based on the flora, which indicated the naturalization of this species.